Identification of Soil Egg Transmitted Helminth on The Nails of Cleaning Workers At TPS Wonocolo District Surabaya City - Damayanti, Chiara Shabrina; Artanti, Dita; Ariana, Diah; Samsudin, Rinza Rahmawati (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background & Objective: In Indonesia, worm infections are still a big problem in public health because the prevalence is still high, namely 45-65%. even in certain areas that have poor environmental sanitation, high heat, and humidity, the prevalence of worm infections can reach 80%. Worm infections can cause a decline in the health condition, nutrition, and productivity of sufferers, resulting in economic losses, due to a decrease in carbohydrates, protein, and blood, which has an impact on reducing the quality of human resources, one of which is transmission through the nails. This study aims to determine whether or not there are Soil Transmitted Helminth (STH) worm eggs in the nails of cleaning workers in Wonocolo District, Surabaya City. Method: The research method used was deposition (sedimentation) centrifugation using 0.25% NaOH solution, which was analyzed descriptively. The sampling technique used was purposive sampling by taking nail samples from 30 waste cleaning officer respondents. Result: The results of the research showed that 17% of the fingernails of waste cleaners were contaminated with Soil Transmitted Helminth (STH) worm eggs, while 83% of nail samples that were not contaminated with Soil Transmitted Helminth (STH) worm eggs were contaminated. Conclusion: Based on the research results, it can be concluded that there are still cleaning workers in Wonocolo District, Surabaya City, who are contaminated with Soil Transmitted Helminth (STH) worm eggs. This happens because their awareness about personal hygiene, sanitation, Clean and Healthy Living Behavior (CHLS), and the use of Personal Protective Equipment (PPE) while working is still lacking.